Clinical value of serum miR-214-3p expression in the diagnosis of type 2 diabetes mellitus and prediction of its chronic complications - Meng Ding; Siyu Yang; Junli Li; Lie Ma; Cunyou Xiong; Jie Zhang (BMC Endocrine Disorders, 2025)
Abstract Background The majority of diabetes cases fall into type 2 diabetes mellitus (T2DM), which is prone to chronic complications that have a long-term impact on patients. The aim of this study was to investigate the diagnostic potential of miR-214-3p in T2DM and its predictive value for chronic complications, providing a novel biomarker for the disease. Methods A total of 156 patients with T2DM and 80 non-T2DM individuals were included. Serum miR-214-3p levels were measured by real-time reverse transcription quantitative PCR (RT-qPCR). The correlation of miR-214-3p with hemoglobin A1c (HbA1c) and low-density lipoprotein cholesterol (LDL-C) was analyzed by Spearman’s rank correlation. The clinical value of miR-214-3p in T2DM was evaluated using the receiver operating characteristic (ROC) curve and logistic regression analysis. Results The serum levels of miR-214-3p were decreased in T2DM patients compared to non-T2DM individuals. A negative correlation was identified between miR-214-3p expression and the levels of HbA1c and LDL-C. miR-214-3p could effectively differentiate T2DM patients from non-T2DM individuals with the area under ROC curve (AUC) of 0.884. Patients with low miR-214-3p expression had a higher incidence of chronic complications. The AUC for miR-214-3p in differentiating between T2DM patients with and without complications was 0.832. Low expression of miR-214-3p was a risk factor linked to the development of chronic complications in patients with T2DM. Conclusion Serum miR-214-3p was downregulated in T2DM and could differentiate T2DM patients from non-T2DM individuals. miR-214-3p was a promising biomarker for predicting the chronic complications of T2DM.